2022
DOI: 10.32598/cjhr.7.1.381.1
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Anger Rumination and Self-Criticism with Social Maladjustment with the Mediating Role of Psychological Flexibility in Adolescent Boys and Girls

Abstract: Background: Anger rumination affects adolescents’ mental health and seriously damages their functions in interpersonal and communication situations and their social adjustment function in various family, academic and occupational situations. Objective: The present study aimed to investigate the relation of anger rumination and self-criticism with social maladjustment with the mediating role of psychological flexibility in adolescent boys and girls in Ahvaz (Iran). Materials & Methods: This descriptive cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mental health problems increase during adolescence, even under normal conditions. About 15-20% of adolescents experience a period of depression in this stage of their lives [17]. It has been reported that about 19% of the emerging adolescents have experienced at least one mental disorder [18].…”
mentioning
confidence: 99%
“…Mental health problems increase during adolescence, even under normal conditions. About 15-20% of adolescents experience a period of depression in this stage of their lives [17]. It has been reported that about 19% of the emerging adolescents have experienced at least one mental disorder [18].…”
mentioning
confidence: 99%